Diagnostic accuracy of rapid one-step PCR assays for detection of herpes simplex virus-1 and -2 in cerebrospinal fluid: a systematic review and meta-analysis. (December 2022) - Vaugon, Esther; Mircescu, Alexandra; Caya, Chelsea; Yao, Mandy; Gore, Genevieve; Dendukuri, Nandini; Papenburg, Jesse
Abstract: Background: Rapid and accurate diagnosis of herpes simplex virus (HSV)-1 and -2 (HSV1/2) in cerebrospinal fluid (CSF) is important for patient management. Objectives: Summarize the diagnostic accuracy of commercial rapid sample-to-answer PCR assays (results in <90 minutes, without a separate nucleic acid extraction step) for HSV1/2 detection in CSF. Data sources: Four databases (MEDLINE, EMBASE, Scopus, and CENTRAL) and five conference abstract datasets from January 2012 to March 2022. Study eligibility criteria: Eligible diagnostic accuracy studies provided sufficient data for the construction of a standard diagnostic accuracy two-by-two table. Participants: Patients with suspected meningitis and/or encephalitis. Tests: FilmArray Meningitis-Encephalitis Panel and Simplexa HSV 1&2 Direct Kit PCR. Reference Standard: Real-time PCR assay. Assessment of risk of bias: Two investigators independently extracted data, rated risk of bias, and assessed quality using QUADAS-2. Methods of data synthesis: Accuracy estimates were pooled using Bayesian random effects models. Results: Thirty-one studies were included (27 FilmArray; 4 Simplexa), comprising 9924 samples, with 95 HSV-1 and 247 HSV-2 infections. Pooled FilmArray sensitivities were 84.3% (95% credible interval, 72.3–93.0) and 92.9% (95% credible interval (CrI), 82.0–98.5) for HSV-1 and HSV-2, respectively; specificities were 99.8% (95% CrI, 99.6–99.9) and 99.9% (95% CrI, 99.9–100). Pooled Simplexa sensitivities were 97.1% (95% CrI, 88.1–99.6) and 97.9% (95% CrI, 89.6–99.9), respectively; specificities were 98.9% (95% CrI, 96.8–99.7) and 98.9% (95% CrI, 97.1–99.7). Pooled FilmArray sensitivities favoured industry-sponsored studies by 10.0 and 13.0 percentage points for HSV-1 and HSV-2, respectively. Incomplete reporting frequently led to unclear risk of bias. Several FilmArray studies did not fully report true negative data leading to their exclusion. Conclusions: Our results suggest Simplexa is accurate for HSV1/2 detection in CSF. Moderate FilmArray sensitivity for HSV-1 suggests additional testing and/or repeat CSF sampling is required for suspected HSV encephalitis when the HSV-1 result is negative. Low prevalence of HSV-1 infections limited summary estimates' precision. Underreporting of covariates limited exploration of heterogeneity.